Initiation Of Pancasila Student Profile In Upper Class Cultural Diversity Of Elementary School Students - Suswandari, M. Pd, Dr. Meidawati; Dwi Anggraeni Siwi; Kevin William Andri Siahaan; Froilan Mobo; Harsono; Ahmad Rosyid (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The purpose of this study was to find out and describe the profile initiation of Pancasila students in the cultural diversity of the upper grades of elementary schools at SD N Demakan 01 Sukoharjo. This research is a qualitative research. This research was conducted at SD N Demakan 01. The determination of informants in this study used a purposive sampling technique. Informants in this study were class IV teachers at SD N Demakan 01 Mojolaban. Data collection techniques in this study are through interviews and documentation. Test its validity using source triangulation technique. Researchers present data using narrative text in the form of interactive data analysis. The results of the study show that the value of diversity or diversity is taught to participants at SD N Demakan 01 Sukoharjo, namely to get used to living in Indonesian society which has a diversity of ethnicities and cultures. Learning activities that can foster a global diversity character at SD N Demakan 01 Sukoharjo include not being picky with friends at school, associating with anyone regardless of religion, ethnicity and race, implementing tolerance, namely teachers and students during group discussions do not blame each other and justifying but respecting differences of opinion when discussing in class, respecting friends at school who are practicing prayer and fasting, studying and preserving cultures from other regions, and efforts to strengthen the climate of diversity in schools through storytelling.